Radio-Immunotherapy-Induced Immunogenic Cancer Cells as Basis for Induction of Systemic Anti-Tumor Immune Responses – Pre-Clinical Evidence and Ongoing Clinical Applications - Derer, Anja; Deloch, Lisa; Rubner, Yvonne; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo S. (Frontiers in Immunology, 2015)
Radiotherapy (RT) primarily aims to locally destroy the tumor via the induction of DNA damage in the tumor cells. However, so called abscopal, namely systemic and immune mediated effects of RT move over more and more in the focus of scientists and clinicians since combinations of local irradiation with immune therapy have been demonstrated to induce anti-tumor immunity. We here summarize changes of the phenotype and microenvironment of tumor cells after exposure to irradiation, chemotherapeutic agents and immune modulating agents rendering the tumor more immunogenic. The impact of therapy-modified tumor cells and damage associated molecular patterns (DAMPs) on local and systemic control of the primary tumor, recurrent tumors and metastases will be outlined. Finally, clinical studies affirming the bench-side findings of interactions and synergies of radiation therapy and immunotherapy will be discussed. Focus is set on combination of radio(chemo)therapy (RCT) with immune checkpoint inhibitors, growth factor inhibitors and chimeric antigen receptor (CAR) T-cell therapy. Well deliberated combination of RCT with selected immune therapies and growth factor inhibitors bear the great potential to further improve anti-cancer therapies.